The brown bear (Ursus arctos L.) in Trentino, Italy: geographical distribution and population size during 1987-1991 / L'orso bruno (Ursus arctos L.) nel Trentino: distribuzione geografica e consistenza numerica negli anni 1987-1991 - Fabio Osti (Hystrix, the Italian Journal of Mammalogy, 1993)
Abstract The present research on alpine Brown bears (Ursus arctos L.), covers a period of five years (1987-1991) of collection of data about the status of this population in Western Trentino (Northeastern Italy). The last wild brown bears survive in the Alps in a range of about 800 km² in the western province of Trento, on the slopes of the Brenta mountains. At present, only about 240 km² of this area are usually utilized by bear population. Within the last five years the bear population has probably remained stable. About 10 bears are presently believed to live in Trentino, with an annual reproduction until 1989. Riassunto La presente ricerca sulla distribuzione e consistenza numerica dell'Orso bruno (Ursus arctos L.) in Trentino comprende un periodo di cinque anni. Nel Trentino occidentale è ancora presente una piccola popolazione di orsi bruni nelle montagne del gruppo di Brenta su un territorio di circa 800 kmq. Di questi soltanto 240 kmq risultano di importanza primaria per la presenza costante della specie. Negli anni della ricerca la popolazione sembra essersi mantenuta numericamente stabile (circa 10 orsi) con una riproduzione annuale fino al 1989.